'Continental Connotations': European Wine Consumption in 1970s Britain. (November 2020) - Moss, Stella
Abstract : This article considers the significant increase in wine consumption in Britain in the period 1965–85. It explores the social and cultural meanings attached to wine through a case study analysis of Good Housekeeping, a women's magazine aimed at a mainly middle-class readership. The vast majority of wine consumed in Britain at this time was European, the appeal of which was, for many, rooted in an idealised evocation of continental sophistication. In illuminating the development of new socio-cultural habits, this article reveals the influence of continental tourism is bolstering enthusiasm for wine, as well as the impact of greater availability and affordability in popularising consumption.